Perbandingan Keterampilan Gerak Dasar Dribbling Siswa Daerah Rural dan Urban dalam Pembelajaran Bola Basket - Jihan Dwi Wulandari; Muchamad Arif Al Ardha; Nurhasan; Sauqi Sawa Bikalawan; Putri Nur Alifah; Tio Fajar Fitrianto (SPRINTER: Jurnal Ilmu Olahraga, 2026)
The purpose of this study is to examine differences in basic basketball dribbling skills between junior high school (SMP) students in rural and urban areas. This study employed a quantitative approach with a comparative design. The sample consisted of 116 eighth-grade students, including 60 from rural areas and 56 from urban areas, selected using cluster sampling. The research instrument consisted of a basketball dribbling skills test covering six different skill categories with a total of 24 assessment indicators using a dichotomous scale. Data were analyzed using the Kolmogorov-Smirnov normality test and the non-parametric Mann-Whitney test. The findings of this study indicate that students in rural and urban areas exhibit significantly different basketball dribbling skills (p = 0.02). Compared to students in urban areas (M = 89.63; SD = 7.54), students in rural areas demonstrated higher average skills (M = 92.77; SD = 6.58). These results indicate that the development of students’ motor skills is influenced by environmental factors, particularly the amount of physical activity, daily movement experiences, and other external factors. Despite limitations in institutional facilities, the findings of this study suggest that ball dribbling skills can be developed more effectively in remote areas. The implications of this research highlight the importance of an adaptive and contextual approach to physical education teaching, tailored to the characteristics of the students’ environment.